Rider Haggard and the imperial occult : hermetic discourse and Romantic contiguity - Magus, Simon (Brill, 2022)
"This book critically examines the literary oeuvre of H. Rider Haggard, placing it in the nineteenth- century occult milieu in which he wrote, and from which he took ideas which remained with him into the first decades of the twentieth century. Building upon earlier trajectories of Haggard studies, notably postcolonialist, psychoanalytic, and feminist platforms, it critiques and nuances these whilst taking a novel approach in elucidating the religio- philosophical and esoteric ideas which are prolific in his work"-- Provided by publisher.
Keywords: Haggard, H. Rider -- (Henry Rider), -- 1856-1925 -- Criticism and interpretation.; Haggard, H. Rider -- (Henry Rider), -- 1856-1925; Occultism in literature.; Religion in literature.; English literature -- 19th century -- History and criticism.; English literature -- 20th century -- History and criticism.; Authors, English -- Biography.; Religion and culture -- Great Britain -- History -- 19th century.; Egypt -- In literature.; Great Britain -- Colonies -- Religion.; Occultisme dans la littérature.; Religion dans la littérature.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Littérature anglaise -- 20e siècle -- Histoire et critique.; Religion et culture -- Grande-Bretagne -- Histoire -- 19e siècle.; Grande-Bretagne -- Colonies -- Religion.; Authors, English; British colonies; English literature; Literature; Occultism in literature; Religion; Religion and culture; Religion in literature; Egypt; Great Britain; 1800-1999; Biographies; Criticism, interpretation, etc.; History